Spatial overlay of the aerial photo materials with the raster maps of open cartographic services - Піскунов, О.Г.; Юрчук, І. А. (Science-based technologies, 2017)
In the artical the information technology is researched, which provides a spatial overlay of the images received by the camera of an unmanned aerial vehicle, and raster maps of open geographic services. Such software helps to solve issues of actualization of maps, observation of agricultural field yields, creation of terrain photoplanes, monitoring, etc. “The Maps Snapshot Comlex Suite” is developed in C # using .NET 4.0. All the algorithms that were used during the development of the complex are described in detail, as well as the flow diagrams of the data utilities from which the complex is composed. Despite the fact that the testing of this complex has shown a poorly high speed in real time, the estimates will allow the possibility of its interactive use under conditions of further refinement.